Audit Committee Characteristics on Audit Fees: The Impact of Malaysian Code of Corporate Governance 2007 - Nurul Azlin, Azmi (2009)
This study extends the previous researcher on the audit fees by examining the association between audit committee characteristic and audit fees. The study specifically investigates the impact of the Malaysian Code of Corporate Governance 2007 on the audit committee characteristics (size, independence, meeting, expertise and training). This study as a pioneer studies that examines the effect of audit committee training on audit fees. This finding indicates audit committee expertise is significantly and positively associated with audit fees as measured by professional qualification and experience of the members. While, the others characteristics (size, independence and meeting) are negatively associated with audit fees. However, audit committee training shown a positive relationship with audit fees as measured by financial-related training. This study contributes to the growing of literature by demonstrating the significant of the relevant financial-related training that will give effect to the expertise of audit committee members. The findings are also relevant to the policy-maker and to practitioners in term of best disclosure of the director's training in annual report.